Factores asociados a la percepción de competencias gerenciales en médicos peruanos recién egresados. - Bustamante-García, Mauricio; Inga-Berrospi, Fiorella; Bazán-Guzmán, María; Sofía Cuba-Fuentes, María (Revista del Cuerpo Médico del Hospital Nacional Almanzor Aguinaga Asenjo)
Background: The managerial competences allow the doctor in training to prepare for the insertion in the health system. Objetive: To identify factors associated with the perception of managerial competencies in doctors graduated from the undergraduate medical programs in who participated in the SERUMS 2018-1 process. Material and Methods: Observational analytical cross-sectional study. The questionnaire "How Dutch medical specialists perceive the competencies and training needs of medical residents in healthcare management" was applied to the doctors applying for SERUMS 2018-1. The prevalence ratio (PR) to measure the degree of association between variables was used. Results: Of the 289 doctors surveyed, 13.8% reported having undergone previous training that potentially contributes to their performance as a manager. 35.5% were at the Iow level of the perception of managerial competencies, 74.8% reported having an interest in developing management activities and 97.2% need training in medical management. Sex and previous training that contributes to performance as a manager is significantly associated with the perception of performance of effective managerial functions with a PR 1.66. Conclusions: The perception of developing effective managerial functions associated with sex and previous training.